A good Darwinian? Winwood Reade and the making of a late Victorian evolutionary epic. (June 2015) - Hesketh, Ian
Abstract: In 1871 the travel writer and anthropologist W. Winwood Reade (1838–1875) was inspired by his correspondence with Darwin to turn his narrow ethnological research on West African tribes into the broadest history imaginable, one that would show Darwin's great principle of natural selection at work throughout the evolutionary history of humanity, stretching back to the origins of the universe itself. But when Martyrdom of Man was published in 1872, Reade confessed that Darwin would not likely find him a very good Darwinian, as he was unable to show that natural selection was anything more than a secondary law that arranges all details. When it came to historicising humans within the sweeping history of all creation, Reade argued that the primary law was that of development, a less contentious theory of human evolution that was better suited to Reade's progressive and teleological history of life. By focussing on the extensive correspondence between Reade and Darwin, this paper reconstructs the attempt to make an explicitly Darwinian evolutionary epic in order to shed light on the moral and aesthetic demands that worked to give shape to Victorian efforts to historicise humans within a vastly expanding timeframe. Highlights: I describe the way in which Winwood Reade's evolutionary epic was conceived through his correspondence with Charles Darwin. Reade determined that he could only shed light on human history by placing it in the context of the history of the universe. Even though Reade wanted to write a Darwinian history he ended up conforming to the genre conventions of the evolutionary epic. I suggest that the evolutionary epic is a non-Darwinian genre of science writing.